ADB and Thailand a development partnership toward inclusive growth. (Metro Manila, Philippines Asian Development Bank, 2017)
The partnership between ADB and Thailand has involved both financial and technical cooperation in a wide range of sectors including infrastructure, finance, energy, environment, and regional cooperation and integration. ADB has continued to serve as an important conduit through which Thai public and private sector institutions gain access to the financial support, knowledge and cutting edge expertise that are essential to the country growing and increasingly sophisticated development.
Keywords: Joint ventures -- Thailand; Investment,Foreign -- Economic development; Electronic books